2020
DOI: 10.3389/fnhum.2020.584385
|View full text |Cite
|
Sign up to set email alerts
|

Using Posterior EEG Theta Band to Assess the Effects of Architectural Designs on Landmark Recognition in an Urban Setting

Abstract: The process of urban landmark-based navigation has proven to be difficult to study in a rigorous fashion, primarily due to confounding variables and the problem of obtaining reliable data in real-world contexts. The development of high-resolution, immersive virtual reality technologies has opened exciting new possibilities for gathering data on human wayfinding that could not otherwise be readily obtained. We developed a research platform using a virtual environment and electroencephalography (EEG) to better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…However, our existing sample size of 21 participants is viable for a 0.05 probability of error, a power of 0.80, and an effect size of dz = 0.66. The assumption of the effect size is consistent with the results of similar prior EEG studies, which have generally found a dz between 0.60 and 0.80 [ 34 , 51 , 52 , 53 ].…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…However, our existing sample size of 21 participants is viable for a 0.05 probability of error, a power of 0.80, and an effect size of dz = 0.66. The assumption of the effect size is consistent with the results of similar prior EEG studies, which have generally found a dz between 0.60 and 0.80 [ 34 , 51 , 52 , 53 ].…”
Section: Methodssupporting
confidence: 87%
“…Prior literature has suggested that theta-band dynamics plays an important role in working memory and visual processing [ 53 , 72 , 73 ]. Therefore, an additional and more detailed analysis was conducted to explore the power dynamics of the theta-band over time, comparing the observation condition to the no-observation condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study provided implications for integrating effective wayfinding into the design of interior environments. Further, Rounds et al (2020) examined the effects of urban design on landmark recognition, with a specific focus on the evaluation of salient architectural features. This EEG study investigated neural processes associated with landmark usage and recognition during landmark-based navigation tasks in a virtual urban setting, providing implications for developing better wayfinding systems in urban planning.…”
Section: Landscape Architecture and Interior Designmentioning
confidence: 99%
“…Interesting emotions, distraction, trance, hypnosis, and intense dreams and emotions Better UX affects weaker relative power on the theta rhythms (frontal and parieto-occipital regions) [12]. eta is correlated with UX on navigation and location recall, which can be considered in the virtual environment [64].…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%